Cyberbullying in high school youth: who are more involved, men or women? - Serrano Barquín, Carolina; Morales Reynoso, Tania; Mendoza González, Brenda (IE Revista de Investigación Educativa de la REDIECH, 2021)
Cyberbullying is an aggressive behavior that occurs in virtual environments, which uses Information and Communication Technologies (ICT) as the main tool to hurt other people, exposing victims to an audience that, with their silence, legitimate aggressions. The general purpose of the research is to know if there are differences between men and women in their participation as perpetrators or victims in cyberbullying. It is quantitative research, with a descriptive study and a non-experimental, cross-sectional design. 252 students from a public high school institution in the State of Mexico participated, 129 women and 123 men. An instrument that measures the cyberbullying variable was applied online. The results allow answering the questions this research posed, identifying that both men and women are at the same risk of being victims and aggressors in cyberbullying. The results are discussed based on an ecological perspective by identifying social aspects such as internet access by gender, levels of violence in the country and motivation to exercise cyberbullying.